Evaluation of chimerism with DNA polymorphisms in bone marrow transplantation - (:unkn) unknown (TURKISH J PEDIATRICS, 1997)
Evaluation of chimeric status following allogenic BMT is an important tool for monitoring the replacement of host cells with donor cells and for determining the risk of relapse. Polymorphic DNA sequences can be used as powerful markers in identification of donor/recipient genotype differences, even between close relatives. Polymerase chain reaction (PCR) amplification of three variable number of tandem repeat (VNTR) loci and five single-locus polymorphisms (SLP) was used to identify chimerism in 40 recipient-donor pairs. Mixed chimerism was present in 11 patients, and complete chimerism in 29. This PCR method is a rapid and sensitive assay to detect engraftment and evaluate relapse potential, and thus is very useful in the clinical management of BMT patients.
Keywords: bone marrow transplantation; chimerism; polymerase chain reaction; polymorphism; VNTR; relapse; POLYMERASE CHAIN-REACTION; CHRONIC MYELOGENOUS LEUKEMIA; MINIMAL RESIDUAL DISEASE; NUCLEOTIDE-SEQUENCES; AMPLIFICATION; CHILDREN; RELAPSE; REGION; LOCUS; VNTR